Disaggregated Analysis of Performances of Grade 12 Learners in Gauteng Province, Republic of South Africa - M.E, Letsoalo (Journal of Education and Vocational Research, 2017)
This paper presents the researchers’ interpretive analysis of data from the main study that was aimed at proposing the method that will plausibly be used to analyse the Grade 12 results and to compare performances of learners between provinces of South Africa. This cross-sectional, quantitative, and ex-post-facto designed study used secondary and clustered data, as supplied by Department of Basic Education through Umalusi council, to compare the likelihood of passing Grade 12 between male and female learners in the Gauteng Province, even after adjusting for school quintile. Thus, this work attempted to model the relation between school resources inputs and school outcomes called educational achievements or academic performances. The dataset contained a total of 98894 (45.44% male and 54.56% female) learners who set for Grade 12 examinations in 2008 academic. The crude estimates indicated that female learners than male learners were significantly 1.035 more likely to pass Grade 12 (OR = 1.035, p = 0.016, 95% CI: 1.006 - 1.065). Also, the school quintile adjusted model indicated that female learners than their male counterparts were significantly 1.040 more likely to pass Grade 12 (OR = 1.040, p = 0.010, 95% CI: 1.009 - 1.072). The significant effect of school quintile favoured female learners (p < 0.001). These results, from disaggregated analysis, indicated that there was sufficient evidence that female than male learners had better chances of passing Grade 12 in Gauteng Province. Therefore, authorities may consider the issue of learner-gender when allocating resources to different school In Gauteng Province.